Preparation method of ultra-pure copper
By using molybdenum oxide as an adsorbent in the electrolytic copper process, silver ions are adsorbed and removed, the problems of low impurity removal efficiency and poor silver removal effect in the prior art are solved, and the stable preparation of high-purity copper and the green and sustainable development of industrial electrolytic copper are achieved.
Patent Information
- Application Number
- CN202411830347.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, there are problems such as low impurity removal efficiency, unstable process, high preparation cost and poor silver removal effect, resulting in large fluctuations in the purity of ultra-high-purity electrolytic copper products and poor quality stability.
Molybdenum oxide is used as the adsorbent for silver ions, and amorphous molybdenum oxide is filled with a double-layer diaphragm bag in the electrolyte, and its good acid resistance and high selectivity adsorption of silver ions is achieved efficiently removing silver ions.
The efficient removal of silver ions in electrolytic copper is achieved, and the ultra-high purity copper-silver content can be stable below 0.02ppm, the purity is above 6N, the process flow is short, the equipment is simple to transform, the operation is simple, and the production efficiency is high, which achieves the green and sustainable development of industrial electrolytic copper.
Smart Images

Figure CN119663374A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal purification, and in particular to a method for preparing ultrapure copper. Background Art
[0002] At present, because the reduction potential of copper in the electrolysis process is close to that of silver, silver is often doped into ultra-high purity copper in the form of a single substance and a copper-silver alloy during the electrolysis process, increasing the production technology cost and difficulty of ultra-pure copper. This is also the main reason for the large fluctuation in the purity of ultra-high purity electrolytic copper products, poor product quality stability, increased unqualified rates, and poor industrial economic benefits.
[0003] At present, in order to eliminate or reduce the silver content in the copper electrolysis process, chemical or physical methods such as additive method, metal replacement method, membrane separation method, etc. are usually used to remove the silver in order to prepare qualified high-purity copper element.
[0004] A method for preparing high-purity copper by electrolyzing a copper salt solution containing an acid (sulfuric acid or nitric acid). The conventional treatment method is to add one or more additives, including amino acids, peptides, gels, etc.; by forming a silver ion complex with a certain stable structure during the electrolysis process, the deposition behavior of silver ions on the cathode is reduced or even eliminated. Secondly, the above-mentioned additives can also be used as smoothing agents to improve the appearance of dendritic copper on the cathode surface and prevent short circuits during the electrolysis process. Due to the difference in impurity content in the original 4N copper, the purity of the high-purity copper product produced by this method fluctuates greatly and the process is unstable.
[0005] The metal replacement method is mainly based on the metal activity sequence table, in descending order of activity: potassium>calcium>sodium>magnesium>aluminum>zinc>iron>tin>lead (>hydrogen)>copper>mercury>silver>platinum>gold. Usually, copper is used as a silver ion replacement agent to remove silver ion impurities in the electrolytic copper process and reduce the silver content in high-purity copper products. However, because the reaction activities of copper and silver are relatively close, the silver ion replacement process is relatively slow, which also leads to an increase in the cost of the actual production process, including an increase in the amount of replacement agent, an extended design of the replacement device, and even a specific temperature environment.
[0006] For the proton exchange membrane separation method, anion and cation exchange membranes or resins are mainly used to initially screen anions and cations, and then a special selective permeable membrane is used to selectively screen the ions of different valence states, thereby reducing the actual high-purity copper and silver impurity content on the cathode. In this scheme, the silver ion content can be maintained at about 0.1 to 0.3 ppm, but due to the high actual cost of ion exchange membranes (2,600 yuan / m 2 ), poor stability and high expansion degree under acidic conditions (pH = 1-2), and poor silver removal effect.
[0007] The existing technology has the defects of low impurity removal efficiency, unstable process, high preparation cost and poor silver removal effect. Therefore, how to quickly and efficiently remove silver impurities and obtain ultra-high purity copper has become a problem that needs to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing ultra-pure copper. The present invention adopts molybdenum oxide as an adsorbent for silver ions, utilizes the good acid resistance of the adsorbent material and the high selectivity of silver ion adsorption, realizes the efficient removal of silver ions in the electrolyte, and obtains ultra-high purity copper by electrolysis.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing ultrapure copper, the preparation method comprising:
[0011] Using crude copper as a consumable anode and a titanium plate as an electrolytic cathode, a double-layer diaphragm bag is used on the outside of the consumable anode to isolate it from the cathode, and amorphous molybdenum oxide is filled between the double-layer diaphragm bags as an adsorbent. Electrolysis is carried out in an electrolyte containing hydrogen peroxide to obtain ultra-pure copper.
[0012] The invention provides a method for preparing high-purity copper by recovering and removing Ag ions under acidic conditions. Amorphous molybdenum oxide is used as an adsorbent. Since the molybdenum element in the amorphous molybdenum oxide exists in both 5-valent and 6-valent states, electron transfer occurs when silver ions are adsorbed on the surface thereof, thereby converting the silver ions into single silver. The adsorbent is placed in a double-layer diaphragm bag for convenient recycling. The purpose of adding hydrogen peroxide in the invention is to remove cuprous ions in the solution.
[0013] This method has the characteristics of short process flow, simple equipment transformation, easy operation and high production efficiency. It can not only stably and efficiently prepare ultra-high purity copper, but also enrich and remove impurity silver ions. The silver content of the ultra-high purity copper produced can be stabilized below 0.02ppm through GD-MS detection, and the purity is above 6N, realizing the green and sustainable development of industrial electrolytic copper.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the crude copper has a purity of 4N grade, where 4N indicates that the copper content of the crude copper is 99.99%.
[0016] Preferably, the double-layer diaphragm bag is made of polyester-cotton or polyester.
[0017] Preferably, the amount of the adsorbent is based on the weight of the crude copper, and 5 to 400 g / t is added, for example, 5 g / t, 10 g / t, 50 g / t, 100 g / t, 120 g / t, 150 g / t, 175 g / t, 200 g / t, 225 g / t, 300 g / t, 350 g / t or 400 g / t, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0018] The unit of dosage is g / t, which represents the amount (in grams) of amorphous molybdenum oxide required for electrolysis of 1 ton of crude copper.
[0019] The amorphous molybdenum oxide in the present invention is used as an adsorbent, and its addition amount affects the adsorption effect of Ag. Too much will result in too much Mo element in the solution entering the high-purity electrolytic copper, and too little will result in too much metallic silver in the high-purity electrolytic copper.
[0020] Preferably, the electrolyte comprises copper nitrate and / or copper sulfate.
[0021] Preferably, the concentration of copper ions in the electrolyte is 50-200 g / L, for example, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L or 200 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0022] Preferably, the concentration of the nitric acid and / or sulfuric acid is 0.5-20 g / L, for example, it can be 0.5 g / L, 1 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 7.5 g / L, 10 g / L, 12.5 g / L, 15 g / L or 20 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the concentration of the hydrogen peroxide is 0.1-2 mL / L, for example, 0.1 mL / L, 0.2 mL / L, 0.3 mL / L, 0.4 mL / L, 0.5 mL / L, 0.755 mL / LL, 1.0 mL / L, 1.5 mL / L or 2.0 mL / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the pH of the electrolyte is 0.4-2, for example, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.25, 1.5, 1.75 or 2, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the electrolysis is preceded by standing.
[0026] Preferably, the standing time is 1 to 5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the current density during electrolysis is 50 to 200 mA / cm 2 , for example, it can be 50mA / cm 2 、60mA / cm 2 , 70mA / cm 2 、80mA / cm 2 , 90mA / cm 2 , 100mA / cm 2 , 110mA / cm 2 , 120mA / cm 2 , 130mA / cm 2 , 140mA / cm 2 , 150mA / cm 2 , 160mA / cm 2 , 170mA / cm 2 , 180mA / cm 2 , 190mA / cm 2 or 200mA / cm 2 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0028] Preferably, the temperature during electrolysis is 20-45°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C or 45°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the preparation method further comprises: taking out the adsorbent after the electrolysis is completed, transferring it to an ammonia solution, stirring it, filtering it to obtain a single substance of Ag; placing the filtrate into a three-electrode system, circulating it by cyclic voltammetry, and recovering the amorphous molybdenum oxide adsorbent.
[0030] The preparation method provided by the present invention can not only obtain ultra-high purity copper by electrolysis, but also recycle and regenerate the adsorbent therein, and utilizes rapid voltage changes, especially near the reduction potential, to help oxidize and reduce Mo with a valence of +5 into amorphous molybdenum oxide with a dual valence state. The recovered amorphous molybdenum oxide can be put into the electrolytic cell again to repeatedly adsorb Ag ions in the solution, and it still has a good adsorption effect, thereby realizing the green and sustainable development of industrial electrolytic copper.
[0031] Preferably, the concentration of the aqueous ammonia solution is 0.1-0.4 M, for example, 0.1 M, 0.15 M, 0.2 M, 0.25 M, 0.3 M, 0.35 M or 0.4 M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the stirring time is 1 to 4 hours, for example, 1 hour, 2 hours, 3 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the working electrode in the three-electrode system comprises conductive glass or conductive carbon cloth.
[0034] Preferably, the reference electrode in the three-electrode system comprises any one of Hg / HgO, Ag / AgCl, Hg / Hg2Cl2 or Hg / HgSO4.
[0035] Preferably, the counter electrode in the three-electrode system comprises any one of a platinum sheet, a graphite rod, a platinum wire or a graphite sheet.
[0036] Preferably, the voltage interval of the cyclic voltammetry is -1.5 V vs RHE to -0.2 V vs RHE.
[0037] Preferably, the scanning speed of the cyclic voltammetry is 20 to 100 mV / s, for example, it can be 20 mV / s, 30 mV / s, 40 mV / s, 50 mV / s, 60 mV / s, 70 mV / s, 80 mV / s, 90 mV / s or 100 mV / s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the number of cycles is 5 to 45 times, for example, 5 times, 10 times, 15 times, 20 times, 25 times, 30 times, 35 times, 40 times or 45 times, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0040] 4N grade crude copper is used as a consumable anode, a double-layer diaphragm bag is used on the outside of the consumable anode to be isolated from the cathode, 5-400 g / t of amorphous molybdenum oxide is filled between the double-layer diaphragm bags as an adsorbent, a titanium plate is used as an electrolytic cathode, and an electrolyte containing 0.1-2 mL / L of hydrogen peroxide, 50-200 g / L of copper ions, and 0.5-20 g / L of nitric acid and / or sulfuric acid is used at a current density of 50-200 mA / cm 2 , electrolysis is carried out at a temperature of 20 to 45°C to obtain ultra-pure copper;
[0041] After the electrolysis is completed, the adsorbent is taken out and transferred to an aqueous ammonia solution with a concentration of 0.1 to 0.4 M. After stirring for 1 to 4 hours, the Ag single substance is obtained by filtration;
[0042] The filtrate is placed in a three-electrode system, with conductive glass or conductive carbon cloth as the working electrode; Hg / HgO as the reference electrode; a platinum sheet or a stone mill as the counter electrode, and cyclic voltammetry is used to cycle 5 to 45 times under the conditions of a voltage range of -1.5 V vs RHE to -0.2 V vs. RHE and a scanning speed of 20 to 100 mV / s to recover an amorphous molybdenum oxide adsorbent.
[0043] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] The present invention provides a method for preparing high-purity copper by recycling and removing Ag ions under acidic conditions, using amorphous molybdenum oxide as an adsorbent, because the molybdenum element in amorphous molybdenum oxide exists in both 5-valent and 6-valent states, causing electron transfer when silver ions are adsorbed on its surface, thereby converting the silver ions into single silver, and placing the adsorbent in a double-layer diaphragm bag for convenient recycling. The method has the characteristics of short process flow, simple equipment modification, simple operation, and high production efficiency, and can not only stably and efficiently prepare ultra-high purity copper, but also realize the enrichment and removal of impurity silver ions. The silver content of the ultra-high purity copper produced can be stabilized below 0.02ppm by GD-MS detection, and the green and sustainable development of industrial electrolytic copper can be realized at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 1 is a schematic diagram of the structure of the electrolytic cell of Example 1 of the present invention; wherein: 11, crude copper; 12, electrolyte; 13, amorphous molybdenum oxide adsorbent; 14, double-layer diaphragm bag; 21, titanium plate. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0048] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0049] Example 1
[0050] This embodiment provides a method for preparing ultrapure copper, the preparation method comprising the following steps:
[0051] (1) Figure 1 The structure of the electrolytic copper reaction cell shown in the figure uses 4N grade crude copper as a consumable anode, a double-layer diaphragm bag is used to isolate the consumable anode from the cathode, 225g / t amorphous molybdenum oxide is filled between the double-layer diaphragm bags as an adsorbent, and a titanium plate is used as an electrolytic cathode. In an electrolyte containing 1mL / L of hydrogen peroxide, 90g / L of copper ions, and 6.3g / L of nitric acid, at a current density of 120mA / cm 2 , electrolysis is carried out at a temperature of 20°C to obtain ultra-pure copper;
[0052] (2) After the electrolysis is completed, the adsorbent is taken out and transferred to a 0.2 M ammonia solution, stirred for 2 h, and then filtered to obtain Ag;
[0053] (3) The filtrate is placed in a three-electrode system, with conductive glass or conductive carbon cloth as the working electrode; Ag / AgCl as the reference electrode; and a platinum sheet or a stone mill as the counter electrode. Cyclic voltammetry is performed under the conditions of a voltage range of -1.5 V vs RHE to -0.2 V vs. RHE and a scan rate of 50 mV / s for 30 cycles to recover an amorphous molybdenum oxide adsorbent.
[0054] Example 2
[0055] This embodiment provides a method for preparing ultrapure copper, the preparation method comprising the following steps:
[0056] (1) 4N grade crude copper was used as the consumable anode. A double-layer diaphragm bag was used to isolate the consumable anode from the cathode. 5 g / t amorphous molybdenum oxide was filled between the double-layer diaphragm bags as an adsorbent. Titanium plates were used as electrolytic cathodes. In an electrolyte containing 0.1 mg / L hydrogen peroxide, 50 g / L copper ions, and 10 g / L sulfuric acid, the current density was 50 mA / cm 2, electrolysis is carried out at a temperature of 45°C to obtain ultra-pure copper;
[0057] (2) After the electrolysis is completed, the adsorbent is taken out and transferred to a 0.2 M ammonia solution, stirred for 4 h, and then filtered to obtain Ag;
[0058] (3) The filtrate is placed in a three-electrode system, with conductive glass or conductive carbon cloth as the working electrode; Hg / HgO as the reference electrode; and a platinum sheet or a stone mill as the counter electrode. Cyclic voltammetry is performed at a voltage range of -1.5 V vs RHE to -0.2 V vs. RHE and a scanning rate of 20 mV / s for 45 cycles to recover an amorphous molybdenum oxide adsorbent.
[0059] Example 3
[0060] This embodiment provides a method for preparing ultrapure copper, the preparation method comprising the following steps:
[0061] (1) 4N grade crude copper was used as the consumable anode, and a double-layer diaphragm bag was used to isolate the consumable anode from the cathode. 400 g / t amorphous molybdenum oxide was filled between the double-layer diaphragm bags as an adsorbent. Titanium plates were used as electrolytic cathodes. In an electrolyte containing 6 mg / L hydrogen peroxide, 120 g / L copper ions, and 0.5 g / L nitric acid, the current density was 150 mA / cm 2 , electrolysis is carried out at a temperature of 35°C to obtain ultra-pure copper;
[0062] (2) After the electrolysis is completed, the adsorbent is taken out and transferred to a 0.4 M ammonia solution, stirred for 1 h, and then filtered to obtain Ag;
[0063] (3) The filtrate is placed in a three-electrode system, with conductive glass or conductive carbon cloth as the working electrode; Hg / Hg2Cl2 as the reference electrode; and a platinum sheet or a stone mill as the counter electrode. Cyclic voltammetry is performed under the conditions of a voltage range of -1.5 V vs RHE to -0.2 V vs. RHE and a scan rate of 100 mV / s, and the amorphous molybdenum oxide adsorbent is recovered and obtained.
[0064] Example 4
[0065] This embodiment provides a method for preparing ultrapure copper, which is different from Embodiment 1 only in that the filling amount of the amorphous molybdenum oxide as an adsorbent in step (1) is 0.1 g / t, and the remaining steps are the same as those in Embodiment 1.
[0066] Example 5
[0067] This embodiment provides a method for preparing ultrapure copper, which is different from Embodiment 1 only in that the filling amount of the amorphous molybdenum oxide as an adsorbent in step (1) is 500 g / t, and the remaining steps are the same as those in Embodiment 1.
[0068] Example 6
[0069] This embodiment provides a method for preparing ultrapure copper. The amorphous molybdenum oxide adsorbent added in step (1) is the amorphous molybdenum oxide adsorbent recovered in Example 1, and the remaining steps are the same as in Example 1.
[0070] Example 7
[0071] This embodiment provides a method for preparing ultrapure copper. The amorphous molybdenum oxide adsorbent added in step (1) is the amorphous molybdenum oxide adsorbent recovered in Example 2, and the remaining steps are the same as in Example 2.
[0072] Example 8
[0073] This embodiment provides a method for preparing ultrapure copper. The amorphous molybdenum oxide adsorbent added in step (1) is the amorphous molybdenum oxide adsorbent recovered in Example 3, and the remaining steps are the same as in Example 3.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing ultrapure copper, which differs from Example 1 only in that an equal mass of activated carbon is added to the double-layer diaphragm bag.
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing ultrapure copper. The method is different from Example 1 only in that the double-layer diaphragm bag and the amorphous molybdenum oxide filled between the diaphragms are replaced by a monovalent ion selective inorganic ion exchange resin.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing ultrapure copper, which differs from Example 1 only in that no hydrogen peroxide is added to the electrolyte.
[0080] Test method: 1. The method for detecting silver content is: glow discharge mass spectrometer GD-MS.
[0081] The test results are shown in Table 1 below.
[0082] Table 1
[0083]
[0084] The test results show that:
[0085] (1) It can be seen from Examples 1 to 3 that the present invention provides a method for recovering and removing Ag ions to prepare high-purity copper under acidic conditions, using amorphous molybdenum oxide as an adsorbent to adsorb Ag ion impurities dissolved out of 4N anode, and placing the adsorbent in a double-layer diaphragm bag for convenient recycling. The method has the characteristics of short process flow, simple equipment modification, simple operation, and high production efficiency. It can not only stably and efficiently prepare ultra-high purity copper, but also realize the enrichment and removal of impurity silver ions. The silver content of the ultra-high purity copper produced can be stably detected by GD-MS to be below 0.02ppm, thereby realizing the green and sustainable development of industrial electrolytic copper.
[0086] (2) By comparing Example 1 with Examples 4 to 5, it can be seen that the present invention further controls amorphous molybdenum oxide as an adsorbent, and its addition amount affects the adsorption effect of Ag. Too little adsorbent causes the Ag ions to be unable to be completely adsorbed, resulting in a decrease in the purity of the electrolytic copper; excessive adsorbent causes more adsorbent to appear in the solution, resulting in a decrease in the purity of the electrolytic copper.
[0087] (3) By comparing Example 1 with Examples 6 to 8, it can be seen that the amorphous molybdenum oxide obtained by recycling in the present invention can still play a good adsorption role during the recycling process and achieve an excellent silver removal effect.
[0088] (4) It can be seen from Example 1 and Comparative Example 1 that the present invention can achieve the technical effect of efficiently removing Ag and enriching Ag by selecting amorphous molybdenum oxide as the adsorbent, while when the adsorbent does not use amorphous molybdenum oxide, it cannot achieve highly efficient removal of Ag.
[0089] (5) It can be seen from Example 1 and Comparative Example 2 that when conventional inorganic ion exchange resin is used to prepare ultrapure copper, it cannot meet the requirement of sufficient and efficient removal of Ag, and the purity of the obtained copper cannot meet the 6N requirement.
[0090] (6) It can be seen from Example 1 and Comparative Example 3 that the purpose of adding hydrogen peroxide in the present invention is to remove nitrite in the solution, and the technical effect of removing pores on the board surface can be achieved. When no hydrogen peroxide is added, the copper board surface obtained is rough and has many pores, which cannot meet the 6N requirement.
[0091] In summary, the present invention provides a method for preparing high-purity copper by recovering and removing Ag ions under acidic conditions, using amorphous molybdenum oxide as an adsorbent, and placing the adsorbent in a double-layer diaphragm bag for convenient recycling. The method has the characteristics of short process flow, simple equipment transformation, simple operation, and high production efficiency. It can not only stably and efficiently prepare ultra-high purity copper, but also realize the enrichment and removal of impurity silver ions. The silver content of the ultra-high purity copper produced can be stabilized below 0.02ppm by GD-MS detection, thereby realizing the green and sustainable development of industrial electrolytic copper.
[0092] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing ultrapure copper, characterized in that: The preparation method comprises: Using crude copper as a consumable anode and a titanium plate as an electrolytic cathode, a double-layer diaphragm bag is used on the outside of the consumable anode to isolate it from the cathode, and amorphous molybdenum oxide is filled between the double-layer diaphragm bags as an adsorbent. Electrolysis is carried out in an electrolyte containing hydrogen peroxide to obtain ultra-pure copper.
2. The method according to claim 1, characterized in that The purity of the crude copper is 4N grade; Preferably, the double-layer membrane bag is made of polyester-cotton or polyester; Preferably, the amount of the adsorbent used is based on the weight of the crude copper, and is 5 to 400 g / t.
3. The method according to claim 1 or 2, characterized in that: The electrolyte includes copper nitrate and / or copper sulfate; Preferably, the concentration of copper ions in the electrolyte is 50 to 200 g / L; Preferably, the concentration of the nitric acid and / or sulfuric acid is 0.5 to 20 g / L; Preferably, the concentration of the hydrogen peroxide is 0.1 to 2 mL / L; Preferably, the pH of the electrolyte is 0.4-2.
4. The method according to any one of claims 1 to 3, characterized in that: Allowing the electrolysis to stand before the electrolysis; Preferably, the standing time is 1 to 5 hours; Preferably, the current density during electrolysis is 50 to 200 mA / cm 2 ; Preferably, the temperature during electrolysis is 20-45°C.
5. The method according to claim 1, characterized in that The preparation method further comprises: After the electrolysis is completed, the adsorbent is taken out, transferred to an ammonia solution, stirred, and filtered to obtain Ag single substance; the filtrate is placed in a three-electrode system, cyclic voltammetry is used for circulation, and an amorphous molybdenum oxide adsorbent is recovered.
6. The method according to claim 5, characterized in that The concentration of the ammonia solution is 0.1 to 0.4 M; Preferably, the stirring time is 1 to 4 hours.
7. The method according to claim 5 or 6, characterized in that: The working electrode in the three-electrode system comprises conductive glass or conductive carbon cloth; Preferably, the reference electrode in the three-electrode system comprises any one of Hg / HgO, Ag / AgCl, Hg / Hg2Cl2 or Hg / HgSO4; Preferably, the counter electrode in the three-electrode system comprises any one of a platinum sheet, a graphite rod, a platinum wire or a graphite sheet.
8. The method according to any one of claims 5 to 7, characterized in that: The reversible hydrogen electrode potential voltage range of the cyclic voltammetry method is -1.5 V vs RHE to -0.2 V vs RHE.
9. The method according to any one of claims 5 to 8, characterized in that: The scanning speed of the cyclic voltammetry is 20 to 100 mV / s; Preferably, the number of cycles is 5 to 45 times.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The preparation method comprises the following steps: 4N grade crude copper is used as a consumable anode, a double-layer diaphragm bag is used on the outside of the consumable anode to be isolated from the cathode, 0.5-100 g / t of amorphous molybdenum oxide is filled between the double-layer diaphragm bags as an adsorbent, a titanium plate is used as an electrolytic cathode, and an electrolyte containing 0.1-2.0 mL / L of hydrogen peroxide, 50-200 g / L of copper ions, and 0.5-20 g / L of nitric acid and / or sulfuric acid is used at a current density of 50-200 mA / cm 2 , electrolysis is carried out at a temperature of 20 to 45°C to obtain ultra-pure copper; After the electrolysis is completed, the adsorbent is taken out and transferred to an aqueous ammonia solution with a concentration of 0.1 to 0.4 M. After stirring for 1 to 4 hours, the Ag single substance is obtained by filtration; The filtrate is placed in a three-electrode system, with conductive glass or conductive carbon cloth as the working electrode; Hg / HgO or Ag / AgCl or Hg / Hg2Cl2 or Hg / HgSO4 as the reference electrode; a platinum sheet or a graphite rod or a platinum wire or a graphite sheet as the counter electrode, and cyclic voltammetry is used to cycle 5 to 45 times under the conditions of a voltage range of -1.5V vs RHE to -0.2V vs. RHE and a scanning speed of 20 to 100mV / s to recover an amorphous molybdenum oxide adsorbent.